Az irodalmi szövegértelmezés határos határtalanságáról - Bényei, Péter (Studia Litteraria, 2019)
The interpretation of literary texts still hold a pivotal role in the practice of university and secondary literary education, thus in the case of text analysis in educational situation one of the most important responsibilities of the teacher is to improve the interpretative skills of students. My paper undertakes two important tasks in this context. Based upon my experiences with my text analysis seminar course for first-year university students I examine, on the one hand, the fixed patterns with which the amateur interpreter tries to overcome the difficulties of interpretation, which tend to hinder rather than support the dialogue about the text. On the other hand, because it is impossible to create an interpretational formula for all literary works, my most important aim is to introduce how a possible model of interpretation is produced in the process, which can serve as a means for amateur interpreters to overcome the more difficult parts of a dialogue. In both cases I use Zoltán Ambrus’s short story titled “Ninive pusztulása” (“The Demise of Nineveh”) (1892) and its student interpretations fromthe past decade.